A Novel Coupling Pattern in Computational Science and Engineering Software - Kamble, Suraj; Xiaoyu Jin; Nan Niu; Simon, Michelle (2017 IEEE/ACM 12th International Workshop on Software Engineering for Science (SE4Science), 2017)
Computational science and engineering (CSE) software is written by experts of certain area(s). Due to the specialization, existing CSE software may need to integrate other CSE software systems developed by different groups of experts. The coupling problem is one of the challenges for software integration. Here, the coupling we study means the issues involved in integrating 2 legacy codes together, but not the multiphysics coupling where distinct codes are combined in order to model particular phenomena. In this paper, we identify a complex coupling pattern when trying to integrate two CSE software systems. We describe the coupling pattern in detail and show the complexity of resolving such kind of coupling patterns. Our work contributes to area of CSE software since there were few previous studies addressing the coupling problem in CSE domain. Our work will further inspire future research in solving the coupling problem during CSE software integration.